Internationalization of Polish IT Small and Medium Enterprises - Patryk STAWIARSKI; Marta UZNANSKA (Communications of International Proceedings, 2022)
A review of the literature indicates a variety of theoretical models of the internationalization process and its conditions, as well as empirical studies. However, the analysis shows that there is a few researches concerning the strategy of internationalization of SMEs in Poland and the evaluation of the impact of internationalization on their development. SMEs play a crucial role in economy, they are predominant in terms of employment and job creation. The main aim of this research is to examine basic trends of Polish IT SMEs operating over the years.
Keywords: internationalization; IT sector; SMEs; entry strategies